Nanoscale chemistry and atomic-scale microstructure of a bulk Ni3Sn material built using selective laser melting of elemental powder blends. (1st December 2021) - Zhao, Rijie; Yang, Tingting; Liao, Hanlin; Fenineche, Nouredine; Coddet, Christian; Gao, Jianrong
Graphical abstract: Highlights: Ni3 Sn specimens were built using selective laser melting of elemental powder blends. EDS mapping verifies the mesoscopic chemical homogeneity of a specimen. HAADF-STEM study reveals nanoscale chemical and structural inhomogeneities. Melt pools attain a liquid undercooling of 165 K leading to disorder trapping. Abstract: Cubic specimens of the intermetallic Ni3 Sn compound were built using selective laser melting of elemental powder blends. A specimen built at a laser power of 200 W and a scanning speed of 0.5 m/s was determined to have a homogeneous distribution of Ni and Sn on a mesoscopic scale in spite of a 2 at.% Sn deficiency. Characterization of the microstructure using the HAADF-STEM technique reveals a dispersion of ultrafine Ni particles, nanoscale chemical inhomogeneity and the formation of antiphase nanodomains in the matrix of equiaxed Ni3 Sn grains. While a mesoscopic homogeneity of the specimen demonstrates a prospect of additive manufacturing of a bulk intermetallic material using selective laser melting, the nanoscale chemical inhomogeneity indicates a need for a better balance between the melting time and the liquid mixing time of melt pools, perhaps by the use of a scanning speed below 0.5 m/s. The formation of the antiphase nanodomains indicates that melt pools attain a liquid undercooling of 165 K leading to disorder trapping during rapid solidification followed by a disorder-order transition. This progress can be helpful to an understanding of metastable microstructure formation in the selective laser melting technology of other intermetallics.